DSPACE REAL-TIME IMPLEMENTATION FOR CONTROL OF WIND-POWERED WATER PUMPING SYSTEM USING PERMANENT MAGNET SYNCHRONOUS GENERATOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper investigates the control of a wind-powered water-pumping system using a permanent-magnet synchronous generator (PMSG) driven by a wind-turbine emulator. The system consists of an induction motor powered by the PMSG through a back-to-back converter, with AC/DC and DC/AC conversion stages. The first section of this paper discusses the modeling and control of the wind-water pumping system, particularly in rural and remote regions. The performances of the turbine, the PMSG, and the IM Centrifugal pump are analyzed. Simulation results have demonstrated good performance and verified the validity of the proposed pumping system under different operating conditions, including wind speed, rotor reference speed, and torque pump variation. To validate the proposed control method, simulations were conducted in MATLAB/Simulink. In the second part, experimental validation was conducted using the dSPACE 1104 control board, enabling real-time data acquisition and control.
Keywords: Wind energy; Induction motor; Permanent magnet synchronous generator; Centrifugal pump; Turbine; Wind pumping; Back-to-back converter; Indirect field-oriented control (FOC); dSpace1104